The Opportunity for Profit to College Student-AthletesAnalysis Study - Aly, Ezzeldin R.; Elmahdy, Sherin Y. (European Scientific Journal, ESJ, 2024)
According to Romero (2018), NCAA athletes should receive better compensation; he also said that demand for elite professional athletes is related to salary, just as in any professional industry. Collegiate student-athletes devote daily time and energy to completing their profession. The likelihood of a high school student-athlete taking part in a collegiate sport is extremely low. This number drops even more for student-athletes who receive full-ride scholarships. Although some college student-athletes are compensated through educational opportunities or academic scholarships, they still live at or below the national poverty level. The NCAA is a nonprofit organization that regulates collegiate sports. This recent study emphasizes the livelihood of collegiate student-athletes and the rules they must follow; more so, it investigated the possible opportunities that college student-athletes might have. These opportunities may come in the form of future compensation challenges and endorsement opportunities. Additionally, this study looked at the coach’s salaries compared to collegiate student-athletes’ opportunities to profit from their crafts.